Hallux valgus treatment with the Percutaneous Bianchi System: a five-year evaluation - Garcia Moreno, Marcus Vinicius Mota; Marçal Vieira, Túlio Eduardo; Costa Alves, Stephane Mirella; de Vasconcelos Silva, Tércio Manoel (Journal of the Foot & Ankle, 2025)
Objective: The objective of this study was to evaluate the Percutaneous Bianchi System (PBS) technique in the treatment of hallux valgus (HV) and its durability in a five-year postoperative follow-up. Method: Nineteen patients diagnosed with HV underwent surgical treatment using the PBS method, and 17 of them were evaluated radiographically before and after surgery, with a 60-month follow-up. The degree of deformity correction was recorded based on the hallux valgus angle (HVA) and intermetatarsal angle (IMA), to evaluate the durability of correction over time. Results: The HVA and IMA were significantly reduced in the immediate postoperative evaluation and remained so until 60 months after surgery, with little variability in the temporal relationship. Conclusion: The PBS technique proved to be a safe and durable procedure for correction of symptomatic HV, achieving improvement of the deformity, although further studies are needed for greater consistency in recommending the technique. Level of Evidence IV; Therapeutic Studies; Case Series.